Cutaneous adverse events associated with BRAF and MEK inhibitors: a systematic review and meta-analysis - Qian, Junhui; Wan, Jinlong; Yao, Qin; Chen, Yin; Ling, Tao; Zhang, Yuejuan; Tang, Zhihua (Frontiers in Pharmacology, 2024)
Aim Cutaneous adverse events (CAEs) after treatment with BRAF and MEK inhibitors in patients with melanoma remain incompletely characterized. To determine the association of BRAF and MEK inhibitor treatment with CAEs in patients with melanoma compared with BRAF inhibitor alone. Method PubMed, Cochrane, Embase and Web of Science were systematically searched for BRAF and MEK inhibitors from database inception through 10 May 2024. Randomized clinical trials reporting on CAEs in patients with melanoma being treated with BRAF and MEK inhibitors compared with patients with melanoma being treated with BRAF inhibitor monotherapy were selected. Pooled Risk ratios (RRs) and 95% CIs were determined using random-effects analyses. The selected end points were alopecia, cutaneous squamous-cell carcinoma, hyperkeratosis, keratoacanthoma, palmoplantar erythrodysaesthesia syndrome, palmoplantar keratoderma, rash, photosensitivity reaction, and skin papilloma. All-grade and high-grade (≥3) CAEs were recorded. Results Comparing with BRAF and MEK inhibitors, treatment with BRAF inhibitors alone was associated with an increased risk of rash (RR, 0.73; 95% CI, 0.54–0.99; p = 0.039; I2 = 88%), alopecia (RR, 0.28; 95% CI, 0.20–0.41; P < 0.001; I2 = 76%), hyperkeratosis (RR, 0.30; 95% CI, 0.22–0.41; P < 0.001; I2 = 56%), palmoplantar erythrodysaesthesia syndrome (RR, 0.21; 95% CI, 0.10–0.47; P < 0.001; I2 = 81%), palmoplantar keratoderma (RR, 0.39; 95% CI, 0.26–0.57; P < 0.001; I2 = 29%), Skin papilloma (RR, 0.25; 95% CI, 0.12–0.52; P < 0.001; I2 = 77%), cutaneous squamous-cell carcinoma (RR, 0.21; 95% CI, 0.11–0.42; P < 0.001; I2 = 50%), and keratoacanthoma (RR, 0.22; 95% CI, 0.12–0.40; P < 0.001; I2 = 0%). Conclusion Therapy with BRAF and MEK inhibitors was associated with a lower risk of CAEs, especially rash, alopecia, hyperkeratosis, palmoplantar erythrodysaesthesia syndrome, palmoplantar keratoderma, skin papilloma, cutaneous squamous-cell carcinoma, and keratoacanthoma, compared with BRAF inhibitor alone. The risks of photosensitivity reaction was similar between the assessed groups. The findings may help to balance between beneficial melanoma treatment and cutaneous morbidity and mortality.